Radzenie sobie z ambiwalencją w relacjach rodzinnych - Żurek, Aldona (Człowiek i Społeczeństwo, 2025)
Ambivalence occurs in relationships between people connected by a strong social ties. Therefore, it is also a feature of relationships between family members. Relatives connected by an ambivalent relationship experience conflicting emotions. They are also subjected to conflicting expectations and demands, related to their social roles. The article undertakes an analysis of the ways of coping with ambivalence by family members belonging to the same generation, and to the generation of parents and the generation of children. The coping strategies adopted to deal with ambivalence depended on the frequency of contact with the relative, and on the strength of the ties linking the relatives. The majority of respondents maintained ambivalent relationships due to a sense of gratitude toward the relative, or because of family values.